2020
DOI: 10.1039/d0fo01269f
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diets rich in olive oil, palm oil or lard on myokine expression in rats

Abstract: Diets rich in olive oil or palm oil or lard differentially modulate some myokines with anti-inflammatory properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 81 publications
1
6
0
2
Order By: Relevance
“…It is difficult to explain the individual dietary intake of nutrients because they act synergistically to maintain body homeostasis. The study of Gauze-Gnagne et al [49], conducted on rats, assessed the influence of various high-fat diets rich in palm oil or olive oil on the modulation of myokine gene expression. The authors reported that high-fat diets (dependending on the type of fat used) can differentially modulate the expression of some myokines (decreased irisin and increased myonectin levels).…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to explain the individual dietary intake of nutrients because they act synergistically to maintain body homeostasis. The study of Gauze-Gnagne et al [49], conducted on rats, assessed the influence of various high-fat diets rich in palm oil or olive oil on the modulation of myokine gene expression. The authors reported that high-fat diets (dependending on the type of fat used) can differentially modulate the expression of some myokines (decreased irisin and increased myonectin levels).…”
Section: Discussionmentioning
confidence: 99%
“…e fact that the diets in the study did not promote endothelial dysfunction could be explained, on the one hand, by their antioxidant content. OO and PO contain several classes of minor components such as polyphenols, carotenoids, and vitamin E, which have antioxidant properties [48][49][50]. Lard on the market is enriched with gallate, which is a powerful antioxidant [51].…”
Section: Discussionmentioning
confidence: 99%
“…Since polyphenols are present both in EVOO and in OLE, it is possible that these molecules are responsible, at least in part, for the beneficial effects of both nutraceuticals on aging-induced sarcopenia. Indeed, flavonoids have been proposed as potential candidates to treat muscle atrophy due to their role in improving mitochondrial function [ 72 ] and decreasing proteolysis through the downregulation of myostatin [ 73 ] and the atrogenes MURF-1 and atrogin-1 [ 74 ]. Moreover, flavonoids are reported to promote myogenesis, upregulating the protein expression of myogenic markers, such as MyoD and myogenin [ 74 ].…”
Section: Discussionmentioning
confidence: 99%